Особливості вербалізації зовнішніх характеристик людини в англомовних версіях Біблії - Сабадаш, Юлія Олександрівна; Sabadash, Yu. O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено особливості вербалізації зовнішніх характеристик людини в англомовних текстах Біблії. Діахронічний аналіз сакральних текстів розкриває культурно марковану конотацію вербалізантів, що пояснюється змінами в лінгвокультурному середовищі. Надається загальна семантична оцінка диференціації мовних одиниць, що репрезентують зовнішні фізичні характеристики людини в біблійних текстах різних епох. Проведено порівняльний аналіз лексичних субституцій з урахуванням лінгвальніх і екстралінгвальніх чинників. The article attempts to represent the peculiarities of the person’s appearance in the English Bible texts. The diachronic analysis of the sacral texts reveals cultural connotation of the language units with respect to linguocultural changes. The article deals with the general semantic analysis of the language differentiations representing human physical appearance in the English Bible texts of various periods. The substitutions of the lexical units are compared and explained through the linguocultural prism. These substitutions reflect the evolution of a person along with the historical development of human society. The author investigates linguistic factors requiring the changes in the later versions of the Bible among which the evolution of the meaning prevails. Democratization and simplification of the textual content, political correctness of the modern society and feminism are the dominating extralingiustic factors which also demand a range of substitutions in the Holy texts.
Linguistic Means of Appearance Representation in the English Bible Texts
Keywords: вербалізація; instantiation; мовна одиниця; language unit; лінгвокультура; linguocultural